2015
DOI: 10.1016/j.vetmic.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and managing bTB risk: Perspectives from Ireland

Abstract: There is substantial variation in herd risk for bovine tuberculosis (bTB) in Ireland, with most herds playing little to no role in the ongoing endemic. In infected areas, bTB persistence (affecting one or a group of herds) is a key feature of the infection. In this paper, we present our current understanding and management of bTB risk in Ireland, based on a detailed review of research and policy. There is close interaction between science and policy in Ireland, seeking both to understand and effectively manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 58 publications
2
44
0
Order By: Relevance
“…Farmers try to increase herd sizes for increased efficiency gains, but increase in herd size may lead to overcrowding causing enhanced cattle‐to‐cattle transmission of M. bovis . This finding is in agreement with those of similar studies that indicated the association of herd size with the prevalence of BTB (More & Good, ; Pavlik, Matlova, Dvorska, Shitaye, & Parmova, ; Proaño‐Perez et al., ; Wright et al., ), including that of Omer et al. () who identified herd size as one of the major risk factors for SICTT reactivity in the Maekel region, one of our current study areas in Eritrea.…”
Section: Discussionsupporting
confidence: 93%
“…Farmers try to increase herd sizes for increased efficiency gains, but increase in herd size may lead to overcrowding causing enhanced cattle‐to‐cattle transmission of M. bovis . This finding is in agreement with those of similar studies that indicated the association of herd size with the prevalence of BTB (More & Good, ; Pavlik, Matlova, Dvorska, Shitaye, & Parmova, ; Proaño‐Perez et al., ; Wright et al., ), including that of Omer et al. () who identified herd size as one of the major risk factors for SICTT reactivity in the Maekel region, one of our current study areas in Eritrea.…”
Section: Discussionsupporting
confidence: 93%
“…32 A variable incidence of bTB may effect through several modes like the geographical position features; Agroecological system; public health condition for humans and animals; herd size, farm management and grazing practice; age, breed, gender and body condition score of animals; compelled organizing schemes of the veterinary departments; concurrent diseases, host genetic variation, immune suppression, cattle behavior, physiological status, cows scheme form, feeding system, treatments with control program, environments or weather, pathological variations. [33][34][35] Whilst the respiratory disorders, emaciation, rough hair coat, decrease in milk production and presence of reproductive failures shows the most prevalent signs of positive cows in blood and milk groups; the enlargement of lymph nodes, loss of appetites and feces abnormalities manifested the lowers, with presence of some differences between both serum groups. These resultants were approval to studies revealed by various researchers.…”
Section: Discussionmentioning
confidence: 99%
“…In general, sensitivity of official diagnostic tests for M. bovis infection is low, and is affected by several factors [2, 7]. Concurrent parasitic infections (e.g.…”
Section: Discussionmentioning
confidence: 99%